Association of Different Lactate Indices with 30-Day and 180-Day Mortality in Patients with ST-Segment Elevation Myocardial Infarction Treated with Primary Percutaneous Coronary Intervention: A Retrospective Cohort Study - Hu L; Lin W; Xu T; Liang D; Xiang G; Zheng R; Zhou C; Dai Q; Jia D (Dove Medical Press, 2020)
Long Hu,1 Wei Lin,2 Tiancheng Xu,1 Dongjie Liang,1 Guangze Xiang,1 Rujie Zheng,1 Changzuan Zhou,1 Qinxue Dai,3 Danyun Jia3 1Department of Cardiovascular Medicine, The Heart Center, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, Zhejiang, People’s Republic of China; 2Department of Pediatric Intensive Care Unit, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou 325027, Zhejiang, People’s Republic of China; 3Department of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou 325000, Zhejiang, People’s Republic of ChinaCorrespondence: Danyun Jia; Qinxue DaiDepartment of Anesthesiology, The First Affiliated Hospital of Wenzhou Medical University, Nanbaixiang, Ouhai District, Wenzhou City 325000, Zhejiang Province, People’s Republic of ChinaTel/Fax +86-577-88581162Email 529365150@qq.com; 653091408@qq.comBackground: Admission lactate level has been reported as a useful marker of mortality. In this study, we compared the relative value of different lactate indices to predict survival in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI).Methods: This was a retrospective observational study including consecutive patients with STEMI undergoing primary PCI who admitted to the Coronary Care Unit of the First Affiliated Hospital of Wenzhou Medical University between 2014 and 2017. The predictive value of lactate indices for mortality was compared using receiver operator characteristic (ROC) analysis, and DeLong’s test was used to compare the AUC. We compared the AUC between GRACE score and GRACE score + lactate index.Results: A total of 1080 patients were included. Fifty-nine died in 30 days and 68 died in 180 days. Most lactate indices (Lacadm, Lac24max, Lac24min and Lac24tw) were significantly lower in survivors (all P< 0.001). In Cox proportional hazards model, each lactate index showed as an independent factor of 30-day and 180-day mortality except LacΔ. Kaplan–Meier curves demonstrated that the patients of higher lactate indices group had higher rates of mortality (all P< 0.0001, except LacΔ P=0.0485). In receiver operator characteristic analysis, Lac24max was significantly larger than Lacadm(P< 0.001) while the AUC value for Lacadm was similar to Lac24min and Lac24tw. Lac24tw improved the predictive probability of 30-day mortality (P=0.0415). Lac24max improved the predictive probability of GRACE score for both 30-day and 180-day mortality (P< 0.05).Conclusion: In patients with STEMI undergoing primary PCI, most lactate indices are all associated with 30-day and 180-day mortality except LacΔ. In prediction of both 30-day and 180-day mortality, Lac24max is superior to Lacadm and significantly enhances the ability of risk stratification and prognostic evaluation when adding Lac24max to the GRACE score.Keywords: STEMI, lactate indices, hyperlactatemia, mortality